KEANEKARAGAMAN JENIS IKAN HASIL TANGKAPAN SAMPINGAN (BYCATCH) PERIKANAN RAJUNGAN DI TELUK LASONGKO DAN KENDARI SULAWESI TENGGARA - Abdul Hamid; Syamsul Kamri (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2019)
Information regarding the diversity of bycatch from blue swimming crab fishing operations is important in ecosystem-based management and assessment for Marine Stewardship Council (MSC) certification of crab fisheries in Southeast Sulawesi and Indonesia. However, data limitation becomes major challenges. This study aims to specify the types of bycatch caught from blue swimming crab fishing in Lasongko and Kendari Bay Southeast Sulawesi. This research was conducted in March to September 2019. Data was collected from trap and bottom gillnet fishing by using a purposive sampling method on a monthly basis. Bycatch was categorized into two groups, namely economically valuable and discarded, according to the local fishers’ perception. Information was presented both spatially and temporally. The results show that bycatch consists of 66 species including 41 economically valuable and 26 discarded species. Indices of diversity, evenness and dominance of fish were also discussed to describe the ecological conditions. Accordingly, this bycatch composition is able to support the management and assessment of MSC certification of crab fisheries in Southeast Sulawesi. Keywords: bycatch, fish diversity, blue swimming crab fisheries, Southeast Sulawesi.